Inversion method of particle size distribution of milk fat based on improved MPGA - Ding, Guochao; Zhou, Zhen; Wu, Yu; Ji, Peng (Frontiers in Bioengineering and Biotechnology, 2022)
Milk fat’s particle size and distribution not only affect product quality, but also have far-reaching impacts on the economy and society for ensuring food safety. Based on total light scattering method, this paper has studied the inversion method of particle size distribution under dependent mode condition by combining multi-population genetic algorithm (MPGA) with Tikhonov smooth function. It has minimized the influence from light-absorb medium to improve the accuracy of inversion results. The approach introduces Tikhonov smooth function and apparent optical parameters to construct an objective fitness function and weaken the ill condition of the particle size inversion equation. It also introduces MPGA to solve the premature convergence of genetic algorithms. The results show that the relative error of the milk fat simulation solution with a nominal diameter is -3.52%, which meets the national standard of ±8%. Thus, the improved MPGA can be used to reconstruct particle size distribution, with good reliability and stability.